Caracterización cromohipológica y zoométrica de caballos criollos de la provincia de Manabí, Ecuador (FASE III) - Chávez Fernández, Carlos Alberto (2022)
The objective was to evaluate the chromohypology and zoometry of the native horses of the Tosagua canton to contribute to a database that allows establishing the characterization of the Creole biotype equines present in the province of Manabí. 140 horses were used as a study base and zoometric canes and a tape measure were used. Regarding data analysis, the statistical package InfoStat (2016) was used, where descriptive statistics were performed to obtain average, minimum value, maximum value, standard deviation and coefficient of variation. Population averages of head width of 24.26 (±1.23) cm and head length of 59.71 (±2.10) cm, with rump width and length of 43.67 (±2.39) were obtained. cm and 45.02 (±1.95) cm respectively, height at the withers 136.44 (±5.71) cm, height at the croup 135.07 (±5.41) cm, longitudinal diameter 136.99 ( ±5.63) cm, bicostal diameter 33.64 (±4.24) cm, thoracic perimeter 148.47 (±7.94) cm and leg perimeter 18.60 (±0.97) cm. On the other hand, zoometric indices identified the population as dolichocephalic, brevilinear, dolichothoraxic, dolichomorphic, between cane and weight, brachypelvic, and weighing approximately 290 to 334 kg. In the profiles, the rectilinear, pyramidal, dorso-lumbar and normal ventral profile prevailed. Regarding the chromohypological characteristics, a preponderance of brown coat color was found (39.29%) and black coloration in its four hooves (78.57%). Concluding that the population has important similarities with the horses of Creole origin of other similar studies in the country.